Hydroxyl radicals in the tropical troposphere over the Suriname rainforest: airborne measurements - M. Martinez; H. Harder; D. Kubistin; M. Rudolf; H. Bozem; G. Eerdekens; H. Fischer; T. Klüpfel; C. Gurk; R. Königstedt; U. Parchatka; C. L. Schiller; et al. (Atmospheric Chemistry and Physics, 2010)
Direct measurements of OH and HO2 over a tropical rainforest were made for the first time during the GABRIEL campaign in October 2005, deploying the custom-built HORUS instrument (HydrOxyl Radical measurement Unit based on fluorescence Spectroscopy), adapted to fly in a Learjet wingpod. Biogenic hydrocarbon emissions were expected to strongly reduce the OH and HO2 mixing ratios as the air is transported from the ocean over the forest. However, surprisingly high mixing ratios of both OH and HO2 were encountered in the boundary layer over the rainforest. The HORUS instrumentation and calibration methods are described in detail and the measurement results obtained are discussed. The extensive dataset collected during GABRIEL, including measurements of many other trace gases and photolysis frequencies, has been used to quantify the main sources and sinks of OH. Comparison of these measurement-derived formation and loss rates of OH indicates strong previously overlooked recycling of OH in the boundary layer over the tropical rainforest, occurring in chorus with isoprene emission.